A coach's perspective on augmented feedback (and technology) in cricket - Tissera, K.; Orth, D.; Huynh, M.; Benson, A. C. (International Journal of Sports Science & Coaching, 2023)
Coaches utilise augmented feedback to help channel learning and skill acquisition in sports. However, the rationale and pedagogical approaches underpinning feedback (and technology) strategies employed by coaches remain poorly understood. The purpose of this study was to explore cricket coaches understanding towards the role of feedback, and how feedback (and technology) strategies are enacted within practice settings, viewed within pedagogical frameworks. An online questionnaire (Qualtrics) consisted of fixed-text and free-text questions. Fixed-text responses were analysed exploring associations (frequencies, chi-square) or differences (Mann-Whitney U) between coaching groups, with free-text questions examined through reflexive thematic analysis, exploring approaches to presenting athletes with feedback (and technology use). Overall, 134 coaches (94% male, 6% female) aged 18-69 years from 12 countries responded to the questionnaire. Following silhouette and k-modes cluster analysis, results were explored for two coaching groups: community cricket coaches (n = 84, 63%) and higher-performance coaches (n = 50, 37%). Significant differences showed greater coaching experience, qualifications, and time spent coaching per week for the higher-performance coaching group (p < 0.0125), in addition to higher self-efficacy around feedback, albeit with a small effect size (p < 0.001, r = 0.29). Community coaches showed a significant difference in manipulating feedback strategies on motivational factors (p < 0.0125). Reflexive thematic analysis identified different rationales for the perceived role of feedback and use of technology across coaching groups, underpinned by contrasting pedagogical approaches (coach-centred versus athlete-centred). Responses highlighted the co-adaptive properties of coach-athlete dyads (evident in how/why feedback was manipulated). Overall findings present opportunities to further coach education to improve understanding and operationalisation of feedback (and technology).